Shelving Urban Excavations: Revisiting Ottoman and Mandate-Period Archives in Western Asia - Bobou, Olympia; Çağlar, Filiz Tütüncü; Kühn, Miriam; Neil, Eleanor Q.; Raja, Rubina (Journal of Urban Archaeology, 2025)
Abstract This article examines the complex and often fragmented nature of archaeological archives through four case studies: the Istanbul Archaeological Museum; the Museum für Islamische Kunst in Berlin; the Gerasa excavation archives at Yale University; and the Ingholt Archives. These case studies highlight key issues surrounding accessibility, archival organization, digitization, and the role of museums in shaping excavation narratives. The paper situates these archives within their colonial and institutional contexts, emphasizing how administrative policies, geopolitical boundaries, and curatorial decisions influence their structure and availability. It explores the challenges posed by archival dispersion, inconsistent cataloguing, and the selective processes of documentation that shape archaeological knowledge. Additionally, the study critically assesses the impact of digitization, noting both its potential for broader access and its limitations in metadata management and decolonization efforts. Museums, as both collectors and curators of archaeological material, play a crucial role in shaping archival narratives, often reinforcing Western archival standards that can obscure original contexts. By analysing the histories and contemporary functions of these archives, this paper underscores the necessity of re-evaluating archival frameworks to enhance accessibility, foster critical engagement, and develop more inclusive approaches to archaeological knowledge production.